Bibliometric Analysis in Communication for Lobbying and Negotiation - Ayuningtyas, Fitria; Tayibnapis , Radita Gora; Ali, Anuar; Moekahar, Fatmawati (Universitas Terbuka, 2025)
Enhancing communication skills is vital for individuals involved in lobbying and negotiations. Lobbying is a critical aspect of all aspects, including corporations, non-profits, and interest groups that seek to influence policymakers. Effective communication is at the heart of successful lobbying efforts. Negotiation is a critical skill needed for effective management. Based on the GAP analysis executed by the researcher, on the keywords Lobby and Lobby in English and Indonesian words, the researchers conduct analysis beginning with research trends identified from keywords and themes from research titles, as well as abstracts and research contacts, in order to identify publications, as well as the focus and novelty of the research. In prior research utilizing Scopus data, one cluster including four elements was identified, derived from a total of 20,001 publications from 2021 to 2025. Based on the data obtained and the results of the analysis that have been described by researchers here, it can be concluded that lobbying and negotiation in communication science studies have not been discussed much in previous research, making it possible for researchers in the field of communication science to discover new themes or discover novelty of the research.